Research progress of nanomaterials for the diagnosis and treatment of pancreatitis - OUYANG Bingqing; LI Yunfeng; QI Luyao; XU Kailiang (Yixue xinzhi zazhi)
Bad habits such as alcoholism and overeating have led to an increasing prevalence of pancreatitis, which carries a serious disease burden. At present, the connection between nanotechnology and medical research is becoming increasingly close, and many new techniques for the diagnosis and treatment of pancreatitis have been proposed based on nanotechnology. We summarise the indicators of organic, inorganic and bionic cell membrane nano in the diagnosis of various enzymes and in the treatment of acute and chronic pancreatitis. A collated discussion is presented to further explore the diagnostic mechanism of pancreatitis and to provide theoretical support for promoting the conversion of products to clinical applications.